Karakteristik Dewan Direksi dan Pengungkapan Emisi Karbon (Board of Directors Characteristics and Carbon Emission Disclosure) - Arniati, Tutik; Munfaqiroh, Siti; Muslichah, Muslichah (STIE Malangkucecwara, 2025)
This study examined the impact of board size, gender diversity, and board meetings on carbon emission disclosure among ten Indonesian state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange between 2020 and 2024. Purposive sampling was employed, yielding 50 observations. The findings suggest that board size has a significant impact on carbon emission disclosure. The frequency of board meetings does not affect carbon disclosure. Gender diversity has a positive impact on carbon disclosure. These results suggest that the effectiveness of governance in promoting sustainability reporting depends on the board's genuine involvement with environmental issues, and that structural board qualities alone may not guarantee greater environmental transparency.